Dispersal kernel of green rice leafhopper estimated from truncated data. Issue 2 (25th September 2022) - Andow, David A.
Abstract: Characterizing dispersal kernels from truncated data is important for managing and predicting population dynamics. We used mark‐recapture data from 10 previously published replicated experiments at three host plant development stages (seedling, tillering, and heading) to estimate parameters of the normal and exponential dispersal kernels for green rice leafhopper, Nephotettix cincticeps (Uhler). We compared classic statistical methods for estimating untruncated distribution parameters from truncated data with maximum likelihood (MLE) and the method of statistical moments for simulated and empirical data. Simulations showed that both methods provided accurate parameter estimates with similar precision. The method of moments is algebraically complex, but simple to calculate, while the MLE methods require numerical solutions of nonlinear equations. Simulations also showed that accurate, precise estimates of the parameters of the untruncated distributions could be attained even under severe truncation with sufficient numbers of recaptures. Both diffusivity and the exponential mean were higher with later plant growth stage, showing that insects moved farther and faster at the heading stage. Precision of the estimates was not strongly related to percent capture, size of the experimental field, or the number of leafhoppers captured. The leptokurtic exponential kernel fit the data better than the normal kernel for all the experiments. These results support an alternative explanation for the strong density‐dependent population regulation of this species at the heading stage. Instead of leafhopper density per se, the increase in movement at this stage could integrate the populations in the separate fields, leveling densities throughout the landscape. Abstract : Using truncated mark‐recapture data at three host plant development stages (seedling, tillering, and heading), we estimated untruncated parameters of the normal and exponential dispersal kernels for green rice leafhopper by maximum likelihood and the method of moments. We simulated data and showed that both methods provided unbiased estimates of the untruncated parameters. Diffusivity and the exponential mean increased with the rice development stage. These results suggest that the increase in movement could integrate the populations across fields, leveling densities throughout the landscape.